Numerical recovery of Robin boundary from boundary measurements for the Laplace equation - Fang, Weifu; Zeng, Suxing (Journal of computational and applied mathematics, 2009)
Based on an integral equation formulation, we present numerical methods for the inverse problem of recovering part of the domain boundary from boundary measurements of solutions to the Laplace equation on an accessible part of the boundary.